Comparing Cross-National Coverage of Genetically Modified Organisms: A Community Structure Approach. (June 2017) - Pollock, John C.; Peitz, Krysti; Watson, Elizabeth; Esposito, Cara; Nichilo, Phil; Etheridge, James; Morgan, Melissa; Hart-McGonigle, Taylor
A community structure analysis compared cross-national coverage of genetically modified organisms (GMOs) with variations in national-level demographics from 19 newspapers worldwide, yielding combined article "prominence" and "direction" "Media Vector" newspaper scores emphasizing either "favorable" (42%) or "unfavorable" (58%) coverage of GMOs. Regression analysis revealed "poverty level" (24.2% of variance) and "percent of agricultural land" (4.7%) totaled 28.9% of the variance, confirming that "vulnerability" indicators are associated with favorable media coverage of GMOs. Contrary to conventional "guard dog" assumptions that media mirror elite interests, systematic research on demographics and GMO coverage reveals that media can mirror the interests of society's most "vulnerable."